God in My Sporting: A Justification for Christian Experience in Sport - Sean Sullivan (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2010)
Examining the intersection between sport and religious faith can be challenging for kinesiology professionals. Many in academics disregard religious statements and experience as meaningless, unscientific, and even dangerous. Others recognize religious experiences as valid forms of knowledge and opportunities to encounter the sacred. Each of these groups has different explanations of religious experience and the areas of life in which such experience can occur. It is the purpose of this paper to examine the legitimacy of and potential for religious experience in general, as well as Christian religious experience in sport and physical activity. After reviewing previous sport and other literature examining connections between sport and religion, this paper outlines historical and recent challenges to religious knowledge and experience as epistemologically meaningful. A contemporary argument for religious experience as warranted and meaningful is provided, and the final section introduces a Christian understanding of religious experience within physical activity and sport. Infusing physical activity with relevance and meaning derived from religious experience will help in achieving lofty outcomes such as lifelong fitness participation and adherence to exercise programs. Incorporating such a view of sport and physical activity can help make our subject matter relevant to people in a way that transcends content knowledge. One challenge to Christian kinesiology professionals is in presenting these religious opportunities in ways that are inclusive and supportive of other religious faiths.
Keywords: Sport; faith-based; leisure; spirituality